What About the Environment? How the Physical Activity–Related Health Competence Model Can Benefit From Health Literacy Research - Carl, Johannes; Grüne, Eva; Pfeifer, Klaus (Frontiers in Public Health, 2021)
Research cultivates a multitude of frameworks, models, and theories with different determinants internal and/or external to the individual contributing to the understanding and explaining of physical activity levels. The physical activity-related health competence (PAHCO) model can be located at the interface between research of health literacy and physical activity. Due to its primary person orientation, however, the model has not yet undergone discussions on the relevance of the environment. Encouraged by the developments in the area of health literacy, the goal of the present perspective article was to stimulate some initial reflections on potential solutions for the competence-environment relationship within the PAHCO model. We extracted three potential solutions for this issue. Dubbed the solution of integration, we first discussed that the PAHCO model could be placed into overarching, more holistic and abstract models of health-enhancing physical activity, such as the capability approach or the socioecological model. Applying a solution of elaboration, researchers could second substantiate existing components of the PAHCO model, such as control competence or self-regulation competence, by further explanations. Characterizing the solution of extension, it would third be possible to introduce (a) separate, competence component(s) that highlight(s) the manageability of the environment, for instance, by establishing a (socio)ecological competence. The article concludes with a short overview of potential empirical approaches, given their potential to assist researchers in identifying preferences for the theoretical advancement to put the development on a stronger evidence base.